ORAL FOLK ART AND ITS PLACE IN THE MODERN WORLD - Zakirova Dilrabo Khaidarovna (Web of Journals Publishing, 2025)
The article is devoted to the study of oral folk art as the most important part of the cultural heritage of the peoples of the world. The paper examines the main forms of oral creativity, such as fairy tales, myths, legends, proverbs, sayings, songs and riddles, as well as their role in preserving historical memory, education and transmission of moral values. Special attention is paid to the interaction of oral creativity with literature, as well as its function as a means of preserving national identity and spiritual traditions. The article analyzes the processes of preservation and systematization of folk art in the context of scientific research, starting with the works of the first folklore collectors. The influence of modern globalization and urbanization on the loss of traditions and the revival of interest in folklore in recent decades is also discussed. The article highlights the relevance of studying and preserving oral folk art in the context of modern culture.
Keywords: culture and traditions, folklore motifs, ethnography, literary studies, cultural studies, mythology, social aspects of folklore